The catholicity of time in the work of George Mackay Brown. (February 2016) - Goroncy, Jason
This essay introduces and explores some explicitly theological concerns in the work of the Orcadian poet, novelist, and dramatist George Mackay Brown (1921–96). More specifically, its interest is with Brown's presentation and treatment of the notion of time. Drawing on examples from a wide selection of his work, it is argued that Brown's conversion to Roman Catholicism, and in particular his delight in the enchantment of the Mass, allowed him to exploit a distinctly Catholic sacramental theology and aesthetic of creation – its location, people, and history – appraised in light of the Eucharist.